Profound Learning and Transformative Learning: Characteristics and Comparisons - Davin J Carr-Chellman; Michael Kroth; Carol Rogers Shaw (Adult Education Research Conference, 2019)
This exploratory, theoretical study develops the concept of profound learning through a mutual interrogation of the literature and research of transformative learning.
Keywords: Profound learning; profundity; deepening; transformative learning